2003
DOI: 10.1016/s0895-7061(02)03260-0
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of furosemide in uncontrolled hypertension in the elderly: role of renin profiling

Abstract: Many of the elderly hypertensive patients in our study had decreased PRA levels and showed significant reductions in BP after furosemide administration. Despite the associated increases in PRA and SA and decreases in ANP in 67% of patients, diuretic use remains important in the control of hypertension in this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0
3

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 31 publications
1
8
0
3
Order By: Relevance
“…A pathogenic role of fluid retention is suggested by studies demonstrating that successful control of resistant hypertension often requires intensification of diuretic therapy. 12, 14, 28-30 Such a role is further supported by studies linking indices of increased volume expansion to resistant hypertension and reduction in fluid retention to overcoming treatment resistance. For example, Taler et al reported that resistant hypertension was characterized by increased thoracic fluid content as measured by thoracic impedance.…”
Section: Mechanisms: Role Of Excess Fluid Retention Vs Heightened Symentioning
confidence: 92%
“…A pathogenic role of fluid retention is suggested by studies demonstrating that successful control of resistant hypertension often requires intensification of diuretic therapy. 12, 14, 28-30 Such a role is further supported by studies linking indices of increased volume expansion to resistant hypertension and reduction in fluid retention to overcoming treatment resistance. For example, Taler et al reported that resistant hypertension was characterized by increased thoracic fluid content as measured by thoracic impedance.…”
Section: Mechanisms: Role Of Excess Fluid Retention Vs Heightened Symentioning
confidence: 92%
“…16 In a separate study it was reported that increased diuresis with the use of furosemide significantly improved blood pressure control in 12 elderly patients with hypertension whose blood pressure was uncontrolled on multidrug regimens. 121 The above studies indicate that patients with resistant hypertension frequently have inappropriate volume expansion contributing to their treatment resistance such that a diuretic is essential to maximize blood pressure control. In most patients, use of a long-acting thiazide diuretic will be most effective.…”
Section: Diuretic Therapymentioning
confidence: 99%
“…[5][6][7][8][9][10] The National Ambulatory Medical Care Survey (NAMCS), an annual nationally representative sample of office visits in the US, collects blood pressure measurements, diagnoses and medications. We sought to assess the prevalence of resistant hypertension among office visits to physicians who typically manage hypertension, describe trends in physicians' use of recommended medications 2 years after publication of the AHA guidelines, and determine whether use of recommended medications varied by regional-level, physician-level, or patient-level characteristics.…”
Section: Introductionmentioning
confidence: 99%